1997
DOI: 10.1192/apt.3.6.352
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal affective disorder

Abstract: Seasonal affective disorder (SAD) is a recurrent depressive disorder in which episodes occur at a particular time of year. The most frequent variant is winter SAD in which patients become depressed during the autumn or early winter, with remission or conversion to hypomania the following spring. Recognition of winter SAD is important because the diagnosis predicts a good response to the novel treatment of phototherapy. One other variant, summer SAD, has also been described and we will discuss this condition se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…To identify subjects with a seasonal course in the recurrent sample, we used three definitions of seasonality, which were operationalized as follows: Same 90‐day periods: The admission dates of the second and third hospitalization are not more than ±45 days apart from the admission date of the first hospitalization, ignoring the number of years between hospitalizations, that is, ((T1 + 45) modulo 365) < 90 AND ((T2 + 45) modulo 365) < 90, where T1 and T2 are time intervals between the subsequent admissions for given participant in days. This conforms to the ICD‐10 criteria for seasonality, defining that episode onset must occur within separate 90‐day periods Same season: The admission dates of the three hospitalizations all fall within the same season, that is, (a) Dec‐Feb, (b) Mar‐May, (c) Jun‐Aug and (d) Sep‐Nov.…”
Section: Methodsmentioning
confidence: 83%
“…To identify subjects with a seasonal course in the recurrent sample, we used three definitions of seasonality, which were operationalized as follows: Same 90‐day periods: The admission dates of the second and third hospitalization are not more than ±45 days apart from the admission date of the first hospitalization, ignoring the number of years between hospitalizations, that is, ((T1 + 45) modulo 365) < 90 AND ((T2 + 45) modulo 365) < 90, where T1 and T2 are time intervals between the subsequent admissions for given participant in days. This conforms to the ICD‐10 criteria for seasonality, defining that episode onset must occur within separate 90‐day periods Same season: The admission dates of the three hospitalizations all fall within the same season, that is, (a) Dec‐Feb, (b) Mar‐May, (c) Jun‐Aug and (d) Sep‐Nov.…”
Section: Methodsmentioning
confidence: 83%
“…Moreover, pollutant concentration can affect the removal rates. For instance, the removal rates of some anti-inflammatories, antibiotics and antidepressants can decrease in winter, since usually, at this time of the year, the consumption of these compounds increases due to weather-associated health problems, such as flue, rheumatic pain [141,142] or seasonal affective disorder (conditions that have more incidence during specific times of the year, usually in autumn and winter) [143,144]. Vieno et al (2005) reported that the total concentration of the pharmaceuticals ibuprofen, naproxen, ketoprofen, diclofenac and bezafibrate in the effluents of a sewage water treatment plant was 3-5 times higher in winter (about 2500 ng L −1 ) than in the other seasons (about 500−900 ng L −1 ) [145].…”
Section: Removal Of Pharmaceuticals In Wastewater Treatment Plants and Factors That Can Affect Their Removalmentioning
confidence: 99%
“…A quintessential and especially impairing quality of this illness is its high risk of recurrence and persistence. Approximately two-thirds of those diagnosed with SAD will face recurrence of these distressing symptoms the following winter (Rodin 1997). In the five to 11 years following initial diagnosis, 22% to 42% of people still su er from SAD, and 33% to 44% develop a nonseasonal pattern in subsequent episodes; the disorder resolves completely in only 14% to 18% of people with SAD (Magnusson 2005;Schwartz 1996).…”
Section: Description Of the Conditionmentioning
confidence: 99%